Upper limb extravasation of cytotoxic drugs: Results of the saline washout technique in children. (June 2020) - Mas, Virginie; Simon, Anne Laure; Presedo, Ana; Mallet, Cindy; Ilharreborde, Brice; Jehanno, Pascal
Abstract: Purpose: Extravasation of cytotoxic vesicant drugs is a surgical emergency (within six hours) since this incident can lead to severe skin and soft-tissue damage. Outcomes after the saline washout procedure have been extensively described in adults, but rarely in children. The aim of this study was to evaluate the outcome of early saline washout procedure for upper limb cytotoxic drug extravasation in children. Methods: All consecutive children with vesicant drug extravasation were retrospectively reviewed. The saline washout procedure was performed. Cosmetic aspect, residual pain and range of movement were analyzed as well as time to surgery and chemotherapy resumption at last follow-up. Results: Between 2014 and 2018, 13 cytotoxic vesicant drug extravasations occurred (mean age 8 years (sem 5)), including 11 treated by the saline washout procedure. At mean follow-up of 11 months (sem 7), the patients had no or low pain and ranges of movement were fully conserved. Two patients (one within the six hours' delay) had soft-tissue necrosis leading to extensive reconstructive surgery. Conclusion: The saline washout procedure is safe and easy and significantly reduces the incidence of extensive skin damage. Early referral to a specialized department is essential. However, the key parameter remains prevention by educating medical staff and nurses about these injuries and by training them for early and urgent management. Level of Evidence: IV